The Short Video Platform Phenomenon and Its Impact on Pre-teen Children's Behavior: An Empirical Study in Medan City - Annisa Febrina; Annisa Sanny; Dinda Fagita (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the impact of using short video platforms on the behavior of pre-adolescent children in Medan City. The rapid development of social media, especially short video platforms such as TikTok and Instagram Reels, has become an inseparable part of the lives of pre-adolescent children. In this context, this study explores how addiction to short video content affects children's social, emotional, and cognitive behavior. The research method used is a quantitative approach with a survey involving 150 respondents aged 10-12 years from various schools in Medan City. The results of the study indicate that excessive use of short video platforms is correlated with increased impulsive behavior, decreased direct social interaction, and a tendency to imitate trends and lifestyles displayed in video content. In addition, this study also found that the duration of use of this platform is closely related to decreased concentration in learning at school. This study recommends stricter supervision by parents and digital education for pre-adolescent children to minimize the negative impacts of social media use.